FRAMING PRABOWO SUBIANTO PADA PILPRES 2024 DALAM TABLOIDISASI PEMBERITAAN DI DETIK.COM - Khansa Berlian, Dinda; Noor Rakhmad, wiwid; Lukmantoro, Triyono (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
Political news, especially related to the presidential election, should ideally be packaged seriously and substantively because it functions to help the public choose a leader rationally. However, a number of mainstream online media in Indonesia tend to highlight the entertainment and sensational elements displayed by each presidential candidate, especially regarding Prabowo Subianto. This happened to Detik.com which predominantly highlighted the behavior, interesting moments, humor, and conflicts involving Prabowo in the midst of his political activities. With these characteristics, it can be said that tabloidization occurred on Detik.com, where serious political news was packaged in a lighter and more entertaining way, thus reducing its relevance to the public interest. This study uses the framing theory and the framing analysis method of the Zhongdang Pan and Gerald M. Kosicki model to find out how Prabowo Subianto was framed by Detik.com in the tabloidization reporting style in the 2024 presidential election by reviewing the syntactic, script, thematic, and rhetorical structures of each news item. In addition, Carsten Reinemann's tabloidization elements are also used to describe the characteristics of tabloidization on Detik.com based on the dimensions of topic, focus, and style. The framing results will be categorized based on the style dimensions including trivialization, personalization, emotionalization, and dramatization news styles. From the analysis of 30 news items marked